Artists' pub : Artists’ Publications Network and Communication Platform - Studienzentrum für Künstlerpublikationen (2009)
The objective of the “Artists’ Publications Network and Communication Platform” is to facilitate Internet networking between different people involved in the context of artists’ publications. Artists, collectors, dealers, publishers, museums, galleries, academics, students, and any other interested parties will be able to use this platform for disseminating information, networking, and cooperating on topics of relevance to the genre of artists’ publications.